Ասույթի պերլոկուտիվ իմաստի ընկալման և մեկնաբանության հարցերի շուրջ - Արփինե Մադոյան (ՀՀ ԳԱԱ հրատ.)
The author of the article claims that context is the main perlocutionary force indicator. The analysis of the factual material comes to prove that the interpretation of the intended perlocutionary force is conditioned by a number of contextual factors, such as the participants' communicative goals, manner of communication, mutual background knowledge, etc.
Keywords: Philology; Linguistics; Language and Literature